Environmental effects of marine finfish aquaculture (Springer, 2005)
Environmental risks associated with large-scale marine finfish cage aquaculture have led to claims that the long-term sustainability of the industry is in doubt. Methods and models currently used to measure near and far-field environmental effects of finfish mariculture and to assess their implications for management are presented in 20 chapters arranged in four sections (Eutrophication, Sedimentation and Benthic Impacts, Changes in Trophic Structure and Function, and Managing Environmental Risks). Case studies show how models may be used to predict environmental changes and provide management tools to minimize potentially adverse environmental risks. The volume is of interest to those working towards sustainable development of mariculture, including environmental managers and decision-makers with regulatory responsibilities.